Comparison of oral Nano-Curcumin with oral prednisolone on oral lichen planus: a randomized double-blinded clinical trial - Kia, Seyed Javad (BMC Complement Med Ther, 2020)
BACKGROUND: Oral lichen planus (OLP) is a mucocutaneous autoimmune disease with T-cell mediation. Corticosteroids are considered as a first choice in OLP and should be used for a long period with a subsequent increase in dose since the disease has a chronic and recalcitrant nature. There have been efforts to use alternative therapies due to the Corticosteroid’s side effects. Curcumin is a non-toxic natural product with different effects on various oral diseases. It demonstrates antioxidant, anti-inflammatory, antimicrobial, and anticarcinogenic activities. It seems that Curcumin can be used as a proper alternative for Corticosteroid treatments. To overcome limitations in the bioavailability of Curcumin, the therapeutic effect of oral Nano-Curcumin was evaluated for the first time. METHODS: Sixty OLP patients were included in this double-blinded randomized clinical trial. The patients were randomly divided into two groups and received either ‘Nano-Curcumin 80 mg’ or ‘Prednisolone 10 mg’ treatments for 1 month. The patients should take one capsule after having their breakfast. The VAS scale was used to analyze pain severity and burning sensation. To assess lesion size the Thongprasom scale was employed. Repeated measures and independent t-tests, as well as LSD paired-test, were used to analyze the data. RESULTS: Data from 57 patients were analyzed. The level of pain, burning sensation, and OLP lesions decreased in both groups of Curcumin and Prednisolone and no statistically significant difference was observed between the two groups. CONCLUSION: Despite many studies conducted to find an effective approach for managing OLP, the results have often been unsatisfactory. In comparison with previous studies, current results clarify the importance of Nano-Curcumin bioavailability in therapeutic effects. Pain VAS and lesion size were decreased with oral Curcumin. The results have shown that oral Curcumin can be used as an alternative therapy for OLP in patients with the contraindicated Corticosteroids or should be used with caution. Oral Curcumin can be used in preventing the recurrence of OLP lesions after the treatment and initial control. Moreover, the amount of Curcumin dose is more important than its use duration in improving OLP. TRIAL REGISTRATION: IRCT, IRCT20100101002950N5. Registered 9 February 2019, https://www.irct.ir/trial/36704.